Automated and Measured Managerial Systems in the Management of Independent Tourism Villages: A Case Study of Parsingguran II Village, Polung Subdistrict, Humbang Hasundutan Regency - Sinulingga, Samerdanta; Nasution, Vivi Adryani; Meutia, Amalia; Kesuma, Sinar Indra; Tampubolon, Flansius; Marpaung, Jonathan Liviera (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of tourism villages is a key strategy for boosting rural economies in Indonesia, but managing these ventures often faces challenges, particularly in establishing systematized and measurable practices. This study investigates the implementation of an automated managerial system in the Parsingguran II Tourism Village, using a qualitative experimental approach. The research explores how the system influences business operations and stakeholder engagement, focusing on contextual impacts rather than quantitative measures. Through intervention-based experimentation and case studies, the findings indicate that the automated system improves managerial efficiency and fosters a more cohesive stakeholder environment. Recommendations are made for scaling this approach to other rural tourism areas, enhancing sustainability and operational effectiveness.